Eu3+ as a marker for formation of core-shell system: YVO4:SiO2 - L. Robindro Singh (Elsevier, 2017)
Eu3+ doped in core and shell (YVO4:SiO2) nanoparticles show luminescence peaks corresponding to magnetic and electric dipole transitions of Eu3+. When Eu3+ ions occupy Y3+ sites, Eu3+ ions are surrounded by eight O2− ions, which is highly asymmetric (D2d). This asymmetric environment can be used to see amount of Eu3+ ions present in Y3+ sites. When Eu3+ ions are present in shell (SiO2), luminescence intensity is very weak. On further annealing, luminescence intensity increases due to diffusion of Eu3+ ions towards to YVO4 core through pores of SiO2. Distribution of Eu3+ in core and shell are supported by lifetime studies.